Factors Associated with Dengue Fever Prevention Practices (Community Survey in Endemic Areas, Kubu Raya Regency, West Kalimantan Province, Indonesia) - Iskandar Arfan; Ayu Rizky; Andri Dwi Hernawan (Intelektual Pustaka Media Utama, 2022)
Prevention practices and the factors that influence them are important to know for spread control and effective strategic planning. This study aims to find factors related to the practice of preventing dengue fever in people in endemic areas of Kuburaya Regency, West Kalimantan Province, Indonesia. This is an observational study with a cross-sectional design. The research sample was 379 households in endemic areas using a questionnaire. Collecting data using a questionnaire with interviews. Bivariate analysis used chi-square test, multivariate analysis used logistic regression. Most respondents have less prevention practices (59.9%), variables related to dengue fever prevention practices are income, education, knowledge about prevention and health education (mass media), In the regression analysis only variables are education, knowledge about prevention, education mass media health related to dengue fever prevention practices. The results of this study indicate that in formulating an approach to dengue fever prevention, strategies that must be developed in preventing dengue fever are to cultivate prevention practices and increase prevention campaigns using mass media, and can focus on areas that have low education and low knowledge of dengue fever prevention